Lymphatic malformations involving the thorax in children: a retrospective cohort study - Wenting Han; Haiming Yang; Jinrong Liu; Huimin Li; Hui Xu; Hui Liu; Xiaolei Tang; Shunying Zhao (BMC Pulmonary Medicine)
Abstract Background Lymphatic malformations (LMs) involving the thorax are rare, with limited clinical understanding. We aimed to summarize the classification, clinical features, treatment, and prognosis of thoracic LMs, and to improve disease management and patient outcomes. Methods Clinical data and follow-up data obtained from 42 patients with thoracic LMs were reviewed retrospectively at a single center in China. Results Patients were classified into 7 types: 1 with macrocystic LM, 3 with infancy primary chylothorax, 4 with primary lymphedema (PL), and 34 with complicated lymphatic anomalies (CLAs), including 18 with generalized lymphatic anomaly (GLA), 8 with kaposiform lymphangiomatosis (KLA), 6 with central conducting lymphatic anomaly (CCLA), and 2 with Gorham–Stout disease. The specific clinical manifestations included chylothorax (50%), white foamy/jelly-like sputum (47.6%), and plastic bronchitis (7.1%). Imaging findings revealed interlobular septal thickening in 20 patients (47.6%) and ground-glass opacity in 13 (31.0%). Improvements were observed in 16 patients with CLAs who were administered sirolimus, 2 with GLA who were administered sirolimus and bevacizumab, 1 with KLA who was administered trametinib, 6 with CCLA who underwent surgery, 3 with infancy primary chylothorax following dietary treatment, and 1 with macrocystic LM following sclerotherapy. Stabilization occurred in 7 patients (3 with CLAs and 4 with PL) postsurgery. Progression or death was observed in 4 patients with GLA and 3 patients with KLA. Conclusions Different types of thoracic LMs have similar clinical features and imaging manifestations but vary in terms of treatment and prognosis.